Guidelines for auditing process safety management systems (The Center, 1993)
A variety of approaches are given so the reader can select the methodology best suited. It discusses the fundamental skills, techniques, and tools of auditing, and the characteristics of a good process safety management system. And, since information needed for review in the audit may be scattered or undocumented, it offers suggestions on what to look for and where. Whether your company is large or small, whether you are experienced with auditing or just developing a system, consistent use of the techniques presented can significantly improve your audit and your process safety management.